Example of Use Multimedia Projector in Teaching Mathematical Contents in Elementary Education - Dorota Dądzik; Mariusz Portalski (Center for Open and Multimedia Eduacation of the University of Warsaw, 2011)
Last years teachers and university teachers observe substantially negative change of pupils achievements in mathe matical skills range in every level schools and in extents of other branches of science learning. An improvement of this state will require activities for many years, including all students of primary, secondary and college schools. One of a way of improvement teaching results in mathematical contents range, in the lowest educational level, is employing modern methods of education with using facilitating education technical devices. These experimental activities were carried out in Primary School 11 in Plock and as an effect of didactic measurement of results they got high assessments.